Disaster Information Seeking During Disaster: A Survey on How Public Use National Disaster Management Agency Malaysia’s (NADMA) Social Media - Aida Filzah Ramli; Mohammad Rezal Hamzah; Nor’izah Ahmad, (Journal of Human Development and Communication (JoHDeC), 2025)
Social media tools provide the best opportunities to facilitate information dissemination to the public and access them during the disaster. During a disaster, the public keep seeking valuable information on social media from trusted sources to coordinate their actions. This paper presents a study that discovers how the public uses NADMA's social media to access information during a disaster. Hence, this study focuses on National Disaster Management Agency Malaysia (NADMA) regarding disaster situations on social media. This study utilised a quantitative research approach through a simple sampling technique. Besides, an online questionnaire survey was conducted, and 501 respondents were from the public on social media who follow the NADMA's official social media. The term of public’s choice of social media and agencies technical were described. Otherwise, the frequency of the public seeking disaster information on social media was analysed. Types of information seeking by the public on social media were also explored. The results could guide the aspect of information management by disaster management teams on social media during disasters.